(3GdCWQGas - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3BNQgG (B:s
(3hjfJgi HMOjK (B: (3Ef GHf YeQ bQf GdML hGdYeQI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B58 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B116s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs